A parallel algorithm for reconfiguring a multibutterfly network with faulty switches - Goldberg, A.V.; Maggs, B.M.; Plotkin, S.A. (IEEE transactions on computers, 1994)
This paper describes a deterministic algorithm for reconfiguring a multibutterfly network with faulty switches. Unlike previous reconfiguration algorithms, the algorithm is performed entirely by the network, without the aid of any off-line computation, even though many of the switches may be faulty. The algorithm reconfigures an N-input multibutterfly network in O(logN) time. After reconfiguration, the multibutterfly can tolerate f worst-case faults and still route any permutation between some set of N/spl minus/O(f) inputs and N/spl minus/O(f) outputs in O(log N) time.< >